2021
DOI: 10.3390/electronics10060727
|View full text |Cite
|
Sign up to set email alerts
|

Futuristic Trends and Innovations for Examining the Performance of Course Learning Outcomes Using the Rasch Analytical Model

Abstract: The literature on engineering education research highlights the relevance of evaluating course learning outcomes (CLOs). However, generic and reliable mechanisms for evaluating CLOs remain challenges. The purpose of this project was to accurately assess the efficacy of the learning and teaching techniques through analysing the CLOs’ performance by using an advanced analytical model (i.e., the Rasch model) in the context of engineering and business education. This model produced an association pattern between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Realizing the importance of evolving educational and pedagogical conditions, universities and colleges are aiming to include extensive upgrades and to develop exciting technological services [ 1 , 2 , 3 , 4 ]. The concept of Smart Campuses in Smart Cities seeks to integrate beneficial technological interventions such as localization and navigation, asset monitoring, smart attendance, and smart parking systems into the fabric of universities in order to improve learning, research, and managerial and administrative efficiency [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Realizing the importance of evolving educational and pedagogical conditions, universities and colleges are aiming to include extensive upgrades and to develop exciting technological services [ 1 , 2 , 3 , 4 ]. The concept of Smart Campuses in Smart Cities seeks to integrate beneficial technological interventions such as localization and navigation, asset monitoring, smart attendance, and smart parking systems into the fabric of universities in order to improve learning, research, and managerial and administrative efficiency [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to obtain a good data analysis of survey questionnaire, a statistical software for Rasch model analysis named Winstep software V3.72.3 was used. Literature studies showed that the Rasch model has been used in other research fields such as education [32]- [36], food and beverages [23], [37], medical [24], and sport [38] and it was proven capable to measure any subjective assessment. At the same time, Rasch is also capable to convert all ordinal data into ratio data.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of smart technologies and the Internet of Things (IoT) into educational institutions represents a significant step toward meeting the demands of the digital world and preparing students for the future. By embracing these technologies, institutions can enhance learning outcomes, improve resource management, and provide a more efficient and effective educational experience [2][3][4].…”
Section: Introductionmentioning
confidence: 99%